Pelaksanaan Ekstrakurikuler Muhadharah Pondok Pesantren Al-Ma’arif Bukittinggi - Firman Firman; Charles Charles; Iswantir Iswantir; Arifmiboy Arifmiboy (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
The background of writing this thesis is the lack of discipline and responsibility of students in participating in the implementation of this Muhadharah Extracurricular, because some came late when the event even some were not present when the event had started. Therefore the author feels the need to study, how is the Muhadharah extracurricular implementation at MTs. Al-ma'arif Koto Selayan Bukittinggi? The purpose of this study is to find out and obtain data about planning, implementation and evaluation (evaluation) in the implementation of extracurricular activities at MTs. Al-ma'arif Bukittinggi. The type of research that the author uses is descriptive qualitative field research, namely research that done by describing the state of the object at the present time based on the facts that appear as they are. The data sources for this research are school principals, deputy heads of curriculum, deputy heads of student affairs, in particular the supervisors of Muhadharah implementation activities, religious coordinators who participate in managing this Muhadharah Implementation and students who take part in the Muhadharah Extracurricular Implementation at MTs. Al-ma'arif koto selayan. In collecting data, the writer uses observation and interview techniques. While the data processing and analysis techniques that the authors use are data reduction, presenting data, and then verifying and drawing conclusions. Testing the validity of the data by using data triangulation techniques, namely comparing the results of observation data and interview results. Based on the results of the research that the author has done at MTs. Al-ma'arif koto selayan Bukittinggi, it is known that the implementation of this Muhadharah is planned by the Madrasah leadership, namely the school principal, committee and teacher council, then the principal gives authority to one of the teachers as the supervisor of extracurricular implementation Muhadharah, in this planning the teacher does not write down the goals but only verbally, so the Muhadharah Extracurricular Implementation is less effective because of the lack of attention from the coach, and this activity is carried out 1x a week, namely every dawn, Friday until 06-30. The assessment of the Implementation of the Extracurricular Muhadharah is based on the presence of students, activeness, creativity when appearing, from the assessment made by the supervisor it is not fair because the assessment carried out does not write down in detail what form of action the students take. The conclusion from the results of research on the implementation of extracurricular Muhadharah is good but does not meet the theory of good management